Зображення канонічних антикомутаційних співвідношень з умовою ортогональності - Якимів, Р.Я. (Український математичний журнал, 2012)
Изучается класс ∗-представлений ∗-алгебры A₀(d), порожденной соотношениями вида, а именно, получено описание классов унитарной эквивалентности неприводимых ∗-представлений A₀(d) при условии существования j=1,...,d, для которого a²j≠0. We study a class of *-representations of the *-algebra A₀(d) generated by relations of the form and propose a description of the classes of unitary equivalence of irreducible *-representations of A₀(d) such that there exists j = 1, … , d for which a²j≠0.